Mammalian target of rapamycin signaling inhibition ameliorates vascular calcification via Klotho upregulation - Zhao, Yang; Zhao, Ming-Ming; Cai, Yan; Zheng, Ming-Fei; Sun, Wei-Liang; Zhang, Song-Yang; Kong, Wei; Gu, Jun; Wang, Xian; Xu, Ming-Jiang (Kidney international, 2015)
Vascular calcification (VC) is a major risk factor for cardiovascular mortality in chronic renal failure (CRF) patients, but the pathogenesis remains partially unknown and effective therapeutic targets should be urgently explored. Here we pursued the therapeutic role of rapamycin in CRF-related VC. Mammalian target of rapamycin (mTOR) signal was activated in the aortic wall of CRF rats. As expected, oral rapamycin administration significantly reduced VC by inhibiting mTOR in rats with CRF. Further in vitro results showed that activation of mTOR by both pharmacological agent and genetic method promoted, while inhibition of mTOR reduced, inorganic phosphate-induced vascular smooth muscle cell (VSMC) calcification and chondrogenic/osteogenic gene expression, which were independent of autophagy and apoptosis. Interestingly, the expression of Klotho, an antiaging gene that suppresses VC, was reduced in calcified vasculature, whereas rapamycin reversed membrane and secreted Klotho decline through mTOR inhibition. When mTOR signaling was enhanced by either mTOR overexpression or deletion of tuberous sclerosis 1, Klotho mRNA was further decreased in phosphate-treated VSMCs, suggesting a vital association between mTOR signaling and Klotho expression. More importantly, rapamycin failed to reduce VC in the absence of Klotho by using either siRNA knockdown of Klotho or Klotho knockout mice. Thus, Klotho has a critical role in mediating the observed decrease in calcification by rapamycin in vitro and in vivo.